Variation in Soil Microbial Community Structure Associated with Different Legume Species Is Greater than that Associated with Different Grass Species - Zhou, Yang; Zhu, Honghui; Fu, Shenglei; Yao, Qing (Frontiers in Microbiology, 2017)
Plants are the essential factors shaping soil microbial community (SMC) structure. When most studies focus on the difference in the SMC structure associated different plant species, the variation in the SMC structure associated with phylogenetically close species is less investigated. Legume (Fabaceae) and grass (Poaceae) are functionally important plant groups; however, their influences of the SMC structure are seldom compared, and the variation in the SMC structure among legume or grass species is largely unknown. In this study, we grown three legume species vs three grass species in mesocosms, and monitored the soil chemical property, quantified the abundance of bacteria and fungi. The SMC structure was also characterized using PCR-DGGE and Miseq sequencing. Results showed that legume and grass differentially affected soil pH, dissolved organic C, total N content, and available P content, and that legume enriched fungi more greatly than grass. Both DGGE profiling and Miseq-sequencing indicated that the bacterial diversity associated with legume was higher than that associated with grass. When legume increased the abundance of Verrucomicrobia, grass decreased it, and furthermore, linear discriminant analysis identified some group-specific microbial taxa as potential biomarkers of legume or grass. These data suggest that legume and grass differentially select for the SMC. More importantly, clustering analysis based on both DGGE profiling and Miseq-sequencing demonstrated that the variation in the SMC structure associated with three legume species was greater than that associated with three grass species.